Engaged scholarship: Encouraging interactionism in entrepreneurship and small-to-medium enterprise (SME) research. Issue 4 (20th November 2017) - Simba, Amon; Ojong, Nathanael
Abstract : Purpose: The purpose of this paper is to introduce a multi-layered theoretical framework to enable engaged scholarship to develop as a practice in entrepreneurship and small business research. To do so, it illuminates the salient features of engaged scholarship, collaborative learning and actor-network theory (ANT). Design/methodology/approach: The paper follows a narrative or traditional literature review design. Specifically, it adopts a thematic approach for summarising and synthesising a body of literature on engaged scholarship, collaborative learning and ANT with the view to develop a new multi-layered theoretical framework. Findings: Applying the theory of engaged scholarship to pivot entrepreneurship/SME research provides scholars with an opportunity to unlock the theory vs practice paradox. Moreover, engaged scholarship offers valuable instructions for encouraging interactionism between entrepreneurship researchers and practitioners as well as reconcile their polarised views. Co-production and co-creation of knowledge addresses the concerns often raised by the practitioner community regarding the relevance and applicability of academic research to practice. Practical implications: The proposed multi-layered framework provides entrepreneurship researchers, and the practitioner community with a taxonomy to use to encourage a joint approach to research. Developing deep partnerships between academics and practitioners can produce outcomes that satisfy the twin imperatives of scholarship that can be of high quality as well as a value to society. Originality/value: The paper advances the theory and practice of engaged scholarship in new ways that are not common in entrepreneurship/SME research. This enables engaged scholarship to develop as a practice in entrepreneurship and small firms' research. Through applying the proposed multi-layered framework in research, academics can deliver fully developed solutions for practical problems. The framework is useful in the theory vs practice and entrepreneurship researchers vs practitioner debates.